2021
DOI: 10.1093/nar/gkab955
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics and determinants of 2-aminoadenine specificity in DNA polymerase DpoZ of vibriophage ϕVC8

Abstract: All genetic information in cellular life is stored in DNA copolymers composed of four basic building blocks (ATGC-DNA). In contrast, a group of bacteriophages belonging to families Siphoviridae and Podoviridae has abandoned the usage of one of them, adenine (A), replacing it with 2-aminoadenine (Z). The resulting ZTGC-DNA is more stable than its ATGC-DNA counterpart, owing to the additional hydrogen bond present in the 2-aminoadenine:thymine (Z:T) base pair, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…DpoZ enzymes from four different phages, overproduced in E. coli and purified to homogeneity, functionally resemble the Klenow fragment of family A DNA polymerase I, but show significantly higher affinity to dZTP over dATP [ 64 ]. The crystal structure of the apo form of DpoZ from vibriophage ϕVC8 showed that this polymerase is structurally quite a typical member of the A family [ 65 ]. It consists of a polymerase domain with palm, thumb, and fingers subdomains as well as a 3′→5′ exonuclease domain.…”
Section: Unusual Functions and Features Of Recently Discovered Phage-encoded Dna Polymerasesmentioning
confidence: 99%
See 3 more Smart Citations
“…DpoZ enzymes from four different phages, overproduced in E. coli and purified to homogeneity, functionally resemble the Klenow fragment of family A DNA polymerase I, but show significantly higher affinity to dZTP over dATP [ 64 ]. The crystal structure of the apo form of DpoZ from vibriophage ϕVC8 showed that this polymerase is structurally quite a typical member of the A family [ 65 ]. It consists of a polymerase domain with palm, thumb, and fingers subdomains as well as a 3′→5′ exonuclease domain.…”
Section: Unusual Functions and Features Of Recently Discovered Phage-encoded Dna Polymerasesmentioning
confidence: 99%
“…Compared to E. coli Pol I, ϕVC8 DpoZ has three small sequence insertions that form external loops in the palm and fingers domains. However, neither single structural motif nor specific residue(s) in the polymerase domain that could justify the preference for dZTPs during DNA synthesis have been identified [ 65 ]. Therefore, substrate preference may arise from the combination of several structural features.…”
Section: Unusual Functions and Features Of Recently Discovered Phage-encoded Dna Polymerasesmentioning
confidence: 99%
See 2 more Smart Citations
“…They also propose that excision of incorporated dA may be promoted by the 3′-exonuclease activity of DpoZ [27]. However, a close investigation of the exonuclease domain of PhiVC8 DpoZ suggests that the selectivity towards dZTP is not directly encoded in its active site [28].…”
Section: Dztp Polymerizationmentioning
confidence: 99%